Structural, Morphological and Elemental Analysis of Selectively Etched and Exfoliated Ti3AlC2 MAX Phase - Nushrat Jahan; Salim Hussain; Huzef Ur Rahman; Insha Manzoor; Shashank Pandey; Kamran Habib; Syed Kaabir Ali; Reetika Pandita; Chandramani Upadhyay (Journal of Multidisciplinary Applied Natural Science, 2021)
In the present research major focus is on the synthesis of materials that can be easily used in small portable devices and as energy storage devices. Here we focused on a new family of 2D materials Ti3C2 (MXenes). Ti3AlC2 (MAX phase) was intercalated using selective etching of aluminium present in the MAX phase. The etching was done using HF in combination with HCl followed by delaminated in DMSO medium using ultrasonication. The synthesized samples were physically characterized via XRD, SEM, and EDX. The XRD diffractogram confirms the formation of MXene through its characteristic plane (002) arising at 2θ~9°. The morphological study revealed the stacked layered sheet like structure obtained through SEM. The elemental confirmation of removal of aluminium was done as indicated by EDX spectroscopy.